Back to the public? - Bardoel, Jo (Javnost (Ljubljana), 2003)
New responsibility and accountability mechanisms for public broadcasters (PSB), such as the broadcast audits recently introduced in the Netherlands, are meant to modernize the relationship between public broadcasters and their audiences. These new ways of organizing public broadcasting's social responsibility are a response to recent trends in broadcast policies - e.g. the advent of dual broadcast systems and therefore stricter legitimation needs and competition rules for PSBs - as well as more general trends in society - e.g. the end of stable ideologies, individualization processes and the emergence of more self-conscious citizens. Consequently the mission statements of public broadcasters have become much more explicit in recent years, and the same holds for the ways in which they accept public obligations and report about their performance in public. The tradition of political responsibility, based on explicit law and regulation but in practice often a tango of political and broadcasting elites, is now being supplemented by new forms of public accountability in which PSBs try to establish a more direct feedback with the public. The article, finally, looks at the present broadcast assessment process in the Netherlands. Based on both research evidence and personal experience of the author, questions are raised such as: how does it work, what are the first experiences and does it seem to be a viable model for other countries? Despite risks of politicization and bureaucratization, public broadcast assessments promise to offer a useful new instrument for both internal quality control and external legitimation.
Keywords: Nizozemska; radio; mass media; množični mediji; television; televizija; kvaliteta; odgovornost; medijska politika; medijski trg; konkurenca